ACCIDENT AND OCCUPATIONAL INJURY FREQUENCY AND AWARENESS AMONG ADOLESCENT GOODS TRANSPORT WORKERS IN DISTRICT RAWALPINDI - Din, Mohi Ud; Mohsin, Shamaila; Mashhadi, Syed Fawad; Rehman, Mahmood Ur (Pakistan Armed Forces Medical Journal, 2019)
Objective: To determine the frequency and types of different injuries among adolescent goods transport workers, to assess the awareness and work related factors associated with occupational injuries.Study Design: Analytical cross-sectional study.Place and Duration of Study: Study was conducted in Goods Transport Areas in District Rawalpindi, from Jan 2017 to Dec 2017.Material and Methods: Study was conducted among Goods Transport Workers in District Rawalpindi. A sample size of 350 using W.H.O. sample size calculator was taken and non – probability purposive sampling was done. After taking informed consent the data was collected for assessment of occupational injuries. Data were analysed using SPSS version 22. Confidence interval was set to be 95% with 5% margin of error.Results: Total 350 adolescent workers were included in study. Mean age was 16.5 ± 1.7 years and 311 (88.9%) workers worked for more than 8 hours/day. The frequency of occupational injury among goods transport workers was found to be 249 (71.1%). In a proportion of workers 131 (37.4%), hand was the most affected part and laceration was the common type of injury in 126 (36%) workers. Almost half of the sample, 178 (50.9%) workers had awareness about occupational injuries. The majority 324 (92.6%) of the adolescent workers did not use personal protective equipment. Significant associations were found between job satisfaction (p=0.006), working extra hours (p=0.001), job stress (p=0.00) and injury frequency.Conclusion: Injury prevalence among goods transport workers was high. The study revealed that the adolescent workers had high perception of hazards but they were also exposed to hazardous situations more frequently. Many factors related to higher injury frequency including working for extra – hours, irregular shifts, stress at work.